Improvement of nursing students' critical thinking skills through problem-based learning in the People's Republic of China: A quasi-experimental study - Haobin Yuan (2018)
A quasi-experimental, two-group pretest-post-test design was conducted to examine the effect of problem-based learning on the critical thinking skills of 46 Year 2 undergraduate nursing students in the People's Republic of China. The California Critical Thinking Skills Test Form A, Chinese-Taiwanese version was used as both a pretest and as a post-test for a semester-long nursing course. There was no significant difference in critical thinking skills at pretest, whereas, significant differences in critical thinking skills existed between the problem-based learning and lecture groups at post-test. The problem-based learning students had a significantly greater improvement on the overall California Critical Thinking Skills Test, analysis, and induction subscale scores compared with the lecture students. Problem-based learning fostered nursing students' critical thinking skills. © 2008 The Authors Journal Compilation © 2008 Blackwell Publishing Asia Pty Ltd.